Design and Development of a CMS-Based School Website Integrated with a 360° Virtual Tour Using the Waterfall Method at SDN Gadungan 02 - Balya Ahmad Waffa; Saiful Nur Budiman; Wahyu Dwi Puspitasari (Jurnal Ilmiah Multidisiplin Indonesia (JIM-ID), 2026)
The utilization of information technology in education plays a crucial role in supporting the openness and equal distribution of information. SDN Gadungan 02, located in Blitar Regency, does not yet have an official digital platform, resulting in manual and limited methods of information delivery and school promotion. This study aims to design and develop a school website based on a Content Management System (CMS) integrated with a 360° Virtual Tour feature as an informative and interactive digital solution. The methodology used is the Waterfall model, comprising analysis, design, implementation, and testing phases. The technologies employed include React JS for the interface, Express JS and PostgreSQL for the backend, and React-Pannellum for displaying 360° panoramas. The website supports two user roles: admin and general users. Its main feature, the 360° Virtual Tour, allows visitors to explore the school environment online. Blackbox testing using the All-Pair technique showed a success rate of 94.87%, while Whitebox testing with the basis path technique resulted in a Cyclomatic Complexity score of 15, indicating moderate complexity. Closed Beta Testing by IT experts and internal users recorded satisfaction rates of 91.25% and 85%, respectively, while Open Beta Testing with 50 respondents yielded 84.75% satisfaction. The website is considered feasible, functional, accessible, and capable of delivering a strong digital experience. Its presence is expected to support information transformation and enhance the school's image and competitiveness in the digital era.